MODAL SOSIAL PERAWAT PEREMPUAN MENGHADAPI PANDEMI COVID-19 DI RSUD DR. AGOESDJAM KETAPANG - Rupita, Rupita (Regalia: Jurnal Riset Gender dan Anak, 2022)
The coronavirus disease (COVID-19) situation in West Kalimantan is on a worrying threshold. Nurses, doctors and other health workers at the forefront are among the affected components in this pandemic situation. The purpose of this research is to map social models that are strengthening for nurses. In addition to the body’s immunity, social and family strengthening is able to be important as a capital or psychic power. The method in this study is descriptive analysis, with data collection through online interviews. Analysis of research data is carried out in conjunction with data collection, so the triangulation of data used is the triangulation of data sources. The study found that female nurses were in hospitals. Dr. Agoesdjam had a strategy in carrying out tasks during pandemics. They strengthen each other. Here created a sense of mutual belonging between health workers who are the vanguard of Covid-19 at dr. Agoesdjam Ketapang Hospital, with the creation of social capital that is intertwined such as trust between colleagues, share values or share the feeling and existence of social networking bonds